Kebijakan Ekonomi Cina pada Kebijakan Alibaba - Syaiful M; Henry Susanto; Asna Ariz Kawanti; Marzius Insani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
ABSTACT The purpose of this study is to analyze the similarities between Alibaba's economic policies during the Ali Sastroamidjojo 1 Cabinet and the policies of China's First 5-Year Plan. The research method used is historical research. The results show that there are similarities between Alibaba's economic policies and China's First 5-Year Plan economic policies. The equation studied is in the economy of the agricultural sector and medium industry. In the field of agriculture, China is making more modern agriculture for the advancement of its country's agricultural system, this is also done in Alibaba's cabinet, namely by modernizing the agricultural system in Indonesia. In the industrial sector, companies in China are granted credit licenses to nationalize industry in China. In addition, the procurement of taxes and a government system that is centralized to the center makes it easier for the government to regulate the process of nationalizing the economy in China. The conclusion of the study is that the policies in Indonesia and China have many similarities, including the similarity in the ideals of eliminating oppression and realizing social justice. Keywords: Alibaba, China, Economy, Policy